The Effect of Meditation in Insomnia due to Stress: A Case Study - Sujeethasai, K. (Journal of Drug Delivery and Therapeutics, 2020)
Meditation is the seventh of the eight limbs of Yoga in Patanjali's Yoga Sutras, is also called as Dhyana. Meditation is the process of quieting the mind in order to spend time in thought for relaxation or spiritual purposes. Insomnia is a sleep disorder that regularly affects millions of people worldwide due to stress. Causes of insomnia include psychological factors, medications and hormone levels. Yoga aasanas, Pranayama and meditation are commonly using to manage stress. The aim of this study is to evaluate the effect of meditation in a patient suffering from insomnia due to stress. A case study was carried out in District Ayurveda Hospital - Mullaitivu. A 65 years old female patient came to the Out patient Department for sleep disturbance. During the interrogation, found that she was in stress. Meditation technique was demonstrated and advised to visit to the clinic alternative days for 2 weeks. The technique was applied for 30 minutes and she felt calm, relax and sleepiness during the procedure. She advised to do regularly in night times. The patient was relived 50% of stress and could be able sleep well after 2 weeks. According to this study Meditation is good for stress management and can be suggested to the patients who have insomni a due to stress. Further study should be made on large study population, control study and standard meditation protocol for confirmation.
Keywords: Yogic Meditation; Insomnia; Stress